PEDAGOGICAL IMPLICATIONS OF THE MATERIALITY CONCEPT. - Griffin, Charles H. (The Accounting Review, 1959)
Abstract The procedures and methods of professional accountants embrace a multitude of alternative courses of action. Many of these are predicated on considerations other than conformance to accepted theory. Accountants in their efforts to frame a useful definition of materiality have produced many illustrative applications and proposed criteria for measurement but have suggested little in specific identification or delimitation of the concept itself. The central theme of most of these gives emphasis to relative importance or relative magnitude, dependent in large measure on individual value judgments. The interdependence of accounting education and professional practice is conceded and the benefits which accrue to each are compounded by their mutual indebtedness. Formal accounting education may be regarded as an interim experience of comparative short duration which introduces a more lengthy professional work experience. The accounting teacher is encouraged to weigh carefully the collateral effects of its emphasis and to give appropriate recognition also to the importance of precision as a valuable mental discipline.